(untitled) (Journal of Hama University, 2024)
This research deals with Punctuation Marks in the Diwan of Eleven Planets by Mahmoud Darwish as a visual rhythmic component that represents part of the rhythmic formation at the visual level of the poetic text . this necessitated providing a brief definition that explains the concept of visual formation. We also definited Punctuation Marks linguistically and terminologically. Then, We moved to the applied study, adopting the statistical method to moniter the presence of Punctuation Marks in the chosen collection and their distribution among his poems. This is an aspect that must be studied because it is important and it has been discussed before , and it will illuminate an aspect of Darwish’s poetry that has not been previously studied .